Gender equality in government and the quality of ministerial positions held by women - Amarante, Erivelto (2021)
The paper examines gender equality in ministerial positions from the UN database on the recruitment of women to the top echelon of government. Our goal is to measure the degree of prestige of the portfolios considering the classification proposed by Escobar-Lemmon and Taylor-Robinson. We work with the hypothesis that the majority of posts headed by women are of low visibility. The result showed that the most relevant ministries continue to be led by men and that women occupy low-prestige thematic positions.